A New Benzodithiophene‐Based Cruciform Electron‐Donor–Electron‐Acceptor Molecule with Ambipolar/Photoresponsive Semiconducting and Red‐Light‐Emissive Properties. Issue 9 (15th May 2017) - Wang, Zhijie; Liu, Zitong; Gao, Zhenhua; Yang, Sifen; Wang, Yuancheng; Zhang, Guanxin; Zhao, Yongsheng; Zhang, Deqing
Abstract: The rational design of multifunctional materials with both emissive and semiconducting properties remains a challenge. A multifunctional cruciform donor–acceptor (D–A) molecule, 2, 2′‐(((4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b′]dithiophene‐2, 6‐diyl)bis(thiophene‐5, 2‐diyl))bis(methanylylidene))dimalononitrile (BDTTM ), which contains a benzodithiophene as the central core, has been synthesized and, based on the output and transfer characteristics of the corresponding FETs, thin films ofBDTTM exhibited ambipolar semiconducting behavior. Notably, FETs with thin films ofBDTTM showed a photoresponse in both p ‐ and n ‐channels, and drain‐source‐current enhancement under white‐light irradiation could be detected, even at a low light intensity of 0.1 mW cm −2 . Furthermore, BDTTM exhibited red‐light emission both in solution and as a crystalline solid. A microplate ofBDTTM with red‐light emission displayed typical optical waveguiding behavior. Abstract : Ferry cross the Mersey : A new benzodithiophene‐based cruciform donor–acceptor (D–A) molecule has been synthesized, which shows ambipolar/photoresponsive and solid‐state red‐light‐emissive properties.